Detection of Parvalbumin Fish Allergen in Canned Tuna by Real-Time PCR Driven by Tuna Species and Can-Filling Medium - Elif Tugce Aksun Tümerkan (Molecules, 2022)
Canned tuna is considered one of the most popular and most commonly consumed products in the seafood market, globally. However, in past decades, fish allergens have been detected as the main concern regarding food safety in these seafood products and are listed as the top eight food allergies. In the group of fish allergens, parvalbumin is the most common. As a thermally stable and calcium-binding protein, parvalbumin can be easily altered with changing the food matrices. This study investigated the effect of a can-filling medium (tomato sauce, spices, and brine solutions) on the parvalbumin levels in canned tuna. The effect of pH, calcium content, and the DNA quality of canned tuna was also investigated before the parvalbumin-specific encoded gene amplification. The presence of fish allergens was determined by melting curve analyses and confirmed by agarose gel electrophoresis. The obtained results showed that the presence of parvalbumin in commercially canned tuna was driven by can-filling mediums, thermal conductivity, calcium content, and the acidity of various ingredients in food matrices. The intra-specific differences revealed a variation in fish allergens that are caused by cryptic species. This study proved that allergens encoding gene analyses by agarose electrophoresis could be used as a reliable approach for other food-borne allergens in complex food matrices.